2016
DOI: 10.5271/sjweh.3559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a participatory organizational-level occupational health intervention on short-term sickness absence: a cluster randomized controlled trial

Abstract: Effect of a participatory organizational-level occupational health intervention on short-term sickness absence: a cluster randomized controlled trial by Framke E, Sørensen OH, Pedersen J, Rugulies R This RCT showed that pre-school employees participating in an organizational intervention focusing on the core task at work had a statistically significantly lower incidence rate of short-term sickness absence than control group employees during a 29-months follow-up period.Refers to the following texts of the Jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…In a previous article of the same intervention study, we had shown that intervention group participants had a decreased risk of sickness absence during follow-up compared to control group participants [25]. Taken the previous and the current finding together, it seems that the intervention was efficacious with regard to sickness absence but not with regard to job satisfaction, exhaustion and sleep disturbances.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…In a previous article of the same intervention study, we had shown that intervention group participants had a decreased risk of sickness absence during follow-up compared to control group participants [25]. Taken the previous and the current finding together, it seems that the intervention was efficacious with regard to sickness absence but not with regard to job satisfaction, exhaustion and sleep disturbances.…”
Section: Discussionmentioning
confidence: 44%
“…However, one has to be cautious with drawing conclusions by comparing the two analyses, because the two samples were only partly overlapping. In the analysis on sickness absence, we used register data to assess the outcome variable and therefore we were able to analyze sickness absence for all employees at all workplaces, including employees who left the workplace during follow-up (who were excluded on the day they left their workplace) and employees who newly started at a workplace during follow-up (who were included on the day, they entered the workplace) [25]. In the current analysis on job satisfaction, exhaustion and sleep disturbances, register data was not available and therefore the analysis was restricted to employees who filled in the questionnaire at both baseline and follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pioneer intervention study has been described in detail elsewhere (8). Briefly, Pioneer was a cluster randomized controlled trial (RCT) implemented in 78 pre-schools in the Municipality of Copenhagen: 44 pre-schools in the intervention and 34 pre-schools in the control group.…”
Section: Study Design and Samplementioning
confidence: 99%